The market for interfirm asset sales - Hite, Gailen L.; Owers, James E.; Rogers, Ronald C. (Journal of Financial Economics, 1987)
We investigate the valuation consequences of voluntary proposals to sell part or all of a corporation's assets. For partial sell-offs, successful sellers and buyers reap statistically significant abnormal returns of 1.66% and 0.83%, respectively. Unsuccessful sellers realize gains at the bid announcement of 1.41% that are lost at the offer termination. In contrast, proposals to liquidate the firm are associated with significant average abnormal returns of 12.24%. We interpret these findings as evidence that asset sales are associated with the movement of resources to higher-valued uses rather than as evidence of market mispricing before the divestiture announcements.